THE EXPLORATION OF COHESIVE DEVICES IN SYNOPSIS WRITINGS PRODUCED BY ENGLISH STUDY PROGRAM STUDENTS OF UNIVERSITAS GADJAH MADA - Asprilla Aqmarina (SALEE: Study of Applied Linguistics and English Education, 2020)
Cohesive devices in a piece of writing serve to unify sentences within a text. Building upon Halliday and Hasan’s (1976) Cohesion in English, this study aimed to identify and classify cohesive devices and also to discover the effects of cohesion overuse and underuse found in synopsis writings written for Book Report 1 and Book Report 2 assignment. The data were collected from 40 synopsis writings produced by the 4th and 5th semester students of English Study Program of Universitas Gadjah Mada. The data analysis applied a qualitative method and the data collection used purposive sampling technique. The findings showed that reiteration was the most prominently used type and followed by reference, conjunction, and collocation with the frequency 2,193 (56.94%), 1,405 (36.48%), 64 (2.92%), and 252 (6.54%) times respectively. Other types with low occurrences were elliptical and substitutional cohesion that occurred 3 (0.078%) and 2 (0.051%) times respectively. In some cases, students tended to overuse and underuse cohesive devices. In terms of cohesion overuse, in some cases, the use of reiteration leading to lexical redundancy and monotonous sentences. And in cohesion underuse, the lack of using personal reference and temporal conjunction yielding ineffective and less cohesive sentences. Keywords: Cohesive Devices; Discourse Analysis; Synopsis Writings.